Turbine components made of titanium alloys
A tailored titanium alloy composition with optimized elemental ratios and processing enhances isotropic properties and strength, addressing the challenges of temperature variation and durability in gas turbine components.
Patent Information
- Application Number
- JP2024092360
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-07
- Filing Date
- 2024-06-06
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing titanium alloys used in gas turbine components face challenges in balancing isotropic properties, low density, resistance to foreign object damage (FOD), repairability, and high cycle fatigue (HCF) capability, while also requiring materials that can withstand varying temperatures across the engine.
A titanium alloy composition is developed with specific weight percentages of aluminum, vanadium, carbon, iron, molybdenum, silicon, oxygen, and nitrogen, optimized for isotropic properties, low density, and improved thick section strength, HCF capability, and ballistic impact resistance, using a forging and heat treatment process to maintain consistency and performance.
The alloy achieves high 0.2% yield strength, ultimate tensile strength, plastic elongation, and ballistic impact resistance, ensuring durability and reliability of turbine components across varying temperatures in gas turbines.
Smart Images

Figure 2024177131000001_ABST
Abstract
Description
[Technical field]
[0001] [Priority information] This application claims priority to U.S. Provisional Patent Application No. 63 / 506,614, filed June 7, 2023, the entire contents of which are incorporated by reference herein for all purposes.
[0002] The present invention relates generally to components formed from titanium alloys. In particular, the components formed from the titanium alloys disclosed herein are particularly suited for use in rotating machines such as gas turbines. [Background technology]
[0003] At least some known rotating machines, such as steam turbine engines and / or gas turbine engines, include various rotor assemblies, such as, but not limited to, fan assemblies, compressors, and / or turbines, each of which includes a rotor assembly. At least some known rotor assemblies include, but are not limited to, components such as disks, shafts, spools, bladed disks ("bladed disks"), seals, and / or bladed integral rings ("bling"), and individual dovetailed connected blades. Such components may be exposed to different temperatures depending on their axial location within the gas turbine engine.
[0004] For example, during operation, at least some known gas turbine engines may be subject to an axial temperature gradient extending along a central longitudinal axis of the engine. Generally, gas turbine engine components are subject to lower operating temperatures toward the front of the engine and higher operating temperatures toward the aft of the engine. As such, known rotor assemblies and / or rotor components are typically fabricated from materials capable of withstanding the highest temperatures expected at their intended locations within the engine. Summary of the Invention
[0005] To accommodate the different temperatures, different engine components are forged from different alloys having different material properties that allow the components to withstand different expected maximum radial and / or axial temperatures. More specifically, known rotating assemblies and / or components are typically forged from a single alloy that can withstand the expected maximum temperature of the entire rotating assembly and / or component, respectively. For example, Ti-17 (Ti-5Al-4Mo-4Cr-2Sn-2Zr), Ti-6246 (Ti-6Al-2Sn-4Zr-6Mo), and Ti-64 (Ti-6Al-4V) may be used for rotating components in gas turbine engines depending on the relative location of the components in the engine.
[0006] Ti-64 is an alpha / beta processed titanium alloy that is highly manufacturable, relatively isotropic, has a relatively low density, is resistant to foreign object damage (FOD), is relatively easy to repair, and is relatively low cost. However, Ti-64 has limited strength in thick sections and high cycle fatigue (HCF) capability. In contrast, Ti-17 and Ti-6246 are beta processed, are not as easy to manufacture, are highly anisotropic (especially ductile) as a result of beta processing, have a high density, are less resistant to FOD (foreign object damage), are not as easy to repair, and are more costly. However, Ti-17 and Ti-6246 have good strength in thick sections, good HCF (high cycle fatigue) capability, and are more heat resistant than Ti-64.
[0007] Therefore, there is a need for a low-cost titanium alloy that combines the excellent properties of Ti-64 (e.g., relatively isotropic properties, relatively low density, resistance to FOD, repairability) with some of the advantages of Ti-17 and Ti-6246 (e.g., thick section strength and HCF). [Brief description of the drawings]
[0008] A full and enabling disclosure of the present invention, including the best mode thereof, directed to one of ordinary skill in the art, is set forth in this specification, which makes reference to the accompanying drawings.
[0009] [Figure 1] FIG. 1 is a cross-sectional view of a gas turbine engine according to an exemplary embodiment of the present disclosure. [Diagram 2] FIG. 2 is an isometric view of an example of a bladed disk turbine component suitable for use in a gas turbine engine such as that shown in FIG. [Diagram 3] FIG. 3 is a two-level cross-sectional view of a bladed disk such as that of FIG. 2, showing an arbitrary location of the weld zone. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Definition] The word "exemplary" is used herein to mean "serving as an example, instance, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Moreover, unless expressly stated otherwise, all embodiments described herein should be considered exemplary.
[0011] The singular forms "a," "an," and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0012] For example, the term "at least one" in the context of "at least one of A, B, and C" refers to A only, B only, C only, or any combination of A, B, and C.
[0013] The phrases "X to Y", "X to Y", and "between X and Y" each refer to a range of values including decimal places (i.e., a range of values that includes both X and Y). Here, and throughout this specification and claims, range limitations are combinable and interchangeable, and such ranges are specified and include all subranges contained therein, unless otherwise indicated by context or language. For example, all ranges disclosed herein include the endpoints, and the endpoints can be combined independently of each other.
[0014] As used herein, the term "substantially free" is understood to mean the total absence of the component or the presence of a trace amount of the component. "Trace amount" refers to a quantitative level of a chemical component that is barely detectable and does not provide any benefit to the functional or aesthetic properties of the subject composition. The term "substantially free" also includes complete absence.
[0015] The term "turbomachine" refers to a machine that includes one or more compressors, a heat generating section (eg, a combustion section), and one or more turbines that together produce a torque output.
[0016] The term "gas turbine engine" refers to an engine that has turbomachinery as all or part of its power source. Examples of gas turbine engines include turbofan engines, turboprop engines, turbojet engines, turboshaft engines, and the like, as well as one or more hybrid-electric versions of these engines.
[0017] In this disclosure, chemical elements are described using common chemical abbreviations as commonly found in the Periodic Table of the Elements, for example, hydrogen is represented by the common chemical abbreviation H and helium is represented by the common chemical abbreviation He.
[0018] The term "yield strength" refers to the stress at which a material begins to exhibit plastic deformation (permanent deformation) without an increase in load. It is the point on the stress-strain curve where the material transitions from elastic (reversible) to plastic (irreversible) deformation. 0.2% yield strength is the strength measured at a plastic strain of 0.2% beyond the yield strength. It is easier and more reproducible to measure than yield strength. 0.2% yield strength is an important parameter in determining the structural integrity and stability of a material under load.
[0019] The term "ultimate tensile strength" ("UTS") is the maximum stress a material can withstand before breaking or failing. It is the highest point on the stress-strain curve and represents the ultimate strength of the material under tensile loading. When the UTS is reached, the material will undergo necking (localized deformation) and ultimately fail.
[0020] The term "plastic elongation" refers to the ability of a material to deform plastically under tensile stress without fracture. It is an important mechanical property that measures the extent to which a material can be permanently deformed without fracture. Ductile materials can undergo large plastic deformations before failure, while brittle materials tend to fail without significant deformation. Plastic elongation is usually measured as the percentage increase in length between two marks made on the gauge length before the test and the final distance between the two marks after the test is completed and the two fractured specimen halves are folded back. A higher percentage of plastic elongation indicates a more ductile material, meaning the metal can deform more before fracture. Conversely, a lower percentage of plastic elongation indicates a less ductile material, meaning the metal is more brittle and tends to fracture without significant plastic deformation.
[0021] "Percent reduction in area" (also written as "%RA") refers to a measurement that quantifies the degree of deformation or plastic flow that occurs in a metal specimen during mechanical testing. When a tensile force is applied to a metal specimen, it undergoes plastic deformation, which elongates and reduces its cross-sectional area. Reduction in area is a measurement of the loss in cross-sectional area after the specimen breaks or breaks during the testing process. Reduction in area is usually expressed as a percentage and is calculated using the following formula: Reduction in area = [(Original Cross-sectional Area - Final Cross-sectional Area) / Original Cross-sectional Area] x 100. A higher reduction in area is more ductile, meaning the metal can deform more before breaking. Conversely, a lower reduction in area is less ductile, meaning the metal is more brittle and tends to break without significant plastic deformation.
[0022] The values of 0.2% yield strength, ultimate tensile strength, plastic elongation, and reduction in area are measured at room temperature (i.e., 20°C-25°C) according to ASTM E8 / E8M, also known as the Standard Test Method for Tensile Testing of Metallic Materials. ASTM E8 / E8M is a widely used standard in the field of materials testing, including alloy characterization, and provides guidelines for performing tensile tests to determine the mechanical properties of metallic materials. In addition to ASTM E8 / E8M, all tensile tests were performed at a controlled strain rate of 0.005 in / in ± 0.002 in / in per minute. After the 0.2 percent yield point was reached and the load stabilized, the crosshead speed was 0.05 ± 0.01 in / in per minute of the length of the reduced portion of the specimen. The plastic elongation and reduction in area (%RA) were measured using the "fitback method," which involves refitting the fractured surface of a broken specimen and measuring the change in length and reduction in cross-sectional area required to calculate these parameters. All tensile tests were performed on bars with a gauge diameter of at least 0.14 inches and a gauge length of at least 0.75 inches.
[0023] "Ballistic resistance" refers to the ability of a material to resist penetration or deformation caused by a projectile or high velocity impact. This is particularly important in applications where protection from bullets, shrapnel, or other projectiles is required. Materials with high ballistic resistance are designed to absorb and dissipate the energy of the impact, reducing damage from the projectile. Ballistic impact damage, or resistance to foreign object damage, was measured using a compressed ballistic device to fire a ball-bearing Cr steel alloy ball having a diameter of about 4.45 mm, a weight of 0.36 g, and a hardness of 55 Rockwell C at a target of the tested alloy having a sample thickness of 0.762 mm at velocities of about 182.9 meters per second to about 304.8 meters per second. The extent of damage was quantified by the sum of the radial crack lengths of the cracks originating from the impact point. For the avoidance of doubt, only the radial crack lengths were summed and circumferential cracks associated with the impact point were not considered.
[0024] The term "weight percent" (abbreviated herein as "wt. %) refers to the concentration of the amount of a particular element in a titanium alloy. Weight percent is the ratio of the weight of the element to the total weight of the titanium alloy, expressed as a percentage. Weight percent is calculated by dividing the weight of the element by the total weight of the titanium alloy and multiplying the result by 100.
[0025] [Detailed Description of the Invention] Reference will now be made in detail to the embodiments of the present disclosure, one or more examples of which are illustrated in the accompanying drawings. The detailed description uses numerical and letter designations to refer to features in the drawings. Like or similar designations in the drawings and description are used to refer to like or similar parts of the present disclosure.
[0026] Turbine components are typically constructed from titanium alloys modified from Ti-64 to maintain the desired properties of Ti-64 (e.g., relatively isotropic properties, relatively low density, resistance to FOD, repairability, and low cost), while improving thick section strength, HCF capability, creep strength, and low deformation after FOD, approaching these advantages of Ti-17 and Ti-6246. The cost of the new and improved Ti-64 alloys can be minimized by engineering the composition to allow for the use of a high percentage of widely available Ti-64 recycled material. Additionally, billet and forging processing approaches as close as possible to Ti-64 allow for large-scale production of such turbine components from titanium alloys while minimizing costs.
[0027] As previously mentioned, turbine components in turbofan engines such as that shown in Figure 1 may be constructed from a titanium alloy that includes, by weight, 5.50% to 6.90% aluminum, 3.50% to 4.50% vanadium, 0.01% to 0.03% carbon, 0.20% to 0.70% iron, 1.00% to 1.50% molybdenum, 0.10% to 0.30% silicon, up to 0.21% oxygen, up to 0.016% nitrogen (e.g., up to 0.015% nitrogen), and the balance titanium. In certain embodiments, the titanium alloy has a 0.2% yield strength of 1000 MPa or more (e.g., 1000 MPa to 1380.0 MPa), an ultimate tensile strength of 1060 MPa or more (e.g., 1060 MPa to 1450 MPa), a plastic elongation of 15.0% or more (e.g., 15.0% to 30.0%), a ballistic impact resistance measured as a crack length of 3.048 mm or less (e.g., 0 mm to 3.048 mm), a reduction in area of 45% or more (e.g., 45% to 75% RA), or any combination of these properties.
[0028] Silicon (Si) is included in titanium alloys to increase their strength, but it has been found that Si contents below 0.10 wt% do not provide sufficient strength to titanium alloys. In addition, it has been found that Si levels above 0.30 wt% decrease ballistic impact resistance, plastic elongation, area reduction, or a combination thereof. It has also been found that increasing Si levels above 0.30 wt% can cause Si segregation problems during solidification of large diameter ingots required for large scale production and manufacturing processes.
[0029] Titanium alloys contain iron (Fe) to increase high temperature strength, widen the temperature window of the α+β phase field, and increase flexibility in hot working. It has been found that a combination of at least 0.20 wt% Fe and 1.00-1.50 wt% Mo provides a desirable balance of strength and plastic elongation. However, a maximum of 0.70 wt% Fe has been found to avoid manufacturing problems in large-scale production and manufacturing processes due to the strong segregation of Fe during solidification of large diameter ingots.
[0030] Molybdenum (Mo) is included in titanium alloys to increase high temperature strength and creep resistance, and to widen the temperature window of the α+β phase field, thereby increasing the flexibility of hot working processes. It has been found that a desirable balance of strength and plastic elongation is achieved by combining at least 1.00 wt% Mo with 0.20 wt% to 0.70 wt% Fe. However, too much Mo in the titanium alloy may reduce the plastic elongation, area reduction, and / or ballistic resistance of the titanium alloy. Thus, it has been found that above 1.50 wt%, the plastic elongation, area reduction, and / or ballistic resistance of the titanium alloy are reduced beyond desirable levels. Increasing the Mo level also leads to an increase in the density of the titanium alloy.
[0031] Nitrogen (N) is present in titanium alloys due to inevitable contamination during the vacuum melting process in the manufacture of titanium alloys. N (nitrogen) increases the strength and hardness of titanium alloys. However, if too much nitrogen is present in the titanium alloy, for example, more than 0.016 wt.% nitrogen (e.g., more than 0.015 wt.% nitrogen), the plastic elongation is reduced, the reduction in area is reduced, and / or the ballistic impact resistance is reduced.
[0032] Oxygen (O) is naturally present in titanium alloys due to titanium's rapid oxidation rate and may be intentionally added to achieve desired chemical properties. However, the amount of O present in the currently disclosed titanium alloys is minimized because it has been found that amounts of O in titanium alloys greater than 0.21 wt.% result in reduced plastic elongation, area reduction, and / or ballistic resistance.
[0033] Carbon (C) is naturally present in titanium alloys due to its low levels in the input materials used in the formulation, and may be added intentionally to meet desired chemistries. A certain amount of C (carbon) above 0.01% by weight is beneficial to the 0.2% yield strength and ultimate tensile strength without reducing plastic elongation, area reduction, and / or ballistic resistance. However, when the amount of carbon present in the alloy exceeds 0.03% by weight, plastic elongation, area reduction, and / or ballistic resistance are reduced.
[0034] In certain embodiments, other elements may be excluded from the titanium alloy to avoid undesirable properties, for example, elements that may prevent large-scale use, such as large-scale manufacturing of turbine components.
[0035] Although copper (Cu) can increase the strength of titanium alloys, it has been found that the presence of Cu can cause severe segregation during the solidification of large diameter ingots, which can lead to chemical reactions and microstructural control issues in large-scale production. Therefore, the inclusion of Cu in titanium alloys results in the formation of inhomogeneous titanium alloy materials, which are unsuitable for the manufacture of turbine components with consistent composition within and across each component. Therefore, titanium alloys are substantially free of Cu, avoiding these issues that prevent the use of titanium alloys in large-scale manufacturing environments.
[0036] Although chromium (Cr) may increase the strength of titanium alloys, it has been found that the presence of Cr can cause segregation during solidification, which can lead to chemical reactions and microstructural control problems in large-scale production. Thus, the presence of Cr in titanium alloys can lead to the formation of inhomogeneous titanium alloy materials that are not suitable for the manufacture of turbine components with consistent composition within and across each component. Therefore, in certain embodiments, the titanium alloys are substantially free of Cr (e.g., below 500 wppm, below 200 wppm or less of residual amounts of Cr present due to the presence of Cr in Ti sponge), avoiding these problems that prevent the use of titanium alloys in large-scale manufacturing environments.
[0037] Although tin (Sn) may increase the strength of the alloy, especially at high temperatures, its presence has been found to reduce plastic elongation, reduce area reduction, and reduce ballistic resistance. Thus, in certain embodiments, to avoid these problems, the titanium alloy is substantially free of Sn.
[0038] Although nickel (Ni) may increase the strength of the alloy, it has been found that the presence of Ni can cause segregation during solidification, which can lead to chemical reactions and microstructural control problems in large-scale production. Thus, the presence of Ni in titanium alloys can lead to the formation of inhomogeneous titanium alloy materials that are not suitable for the manufacture of turbine components with consistent composition within and across each component. Therefore, in certain embodiments, the titanium alloy is substantially free of Ni (e.g., no more than 500 wppm, no more than 200 wppm or less of residual amounts of Ni present due to the presence of Ni in Ti sponge), avoiding these problems that prevent the use of titanium alloys in large-scale manufacturing environments.
[0039] Zirconium (Zr) may increase the strength of titanium alloys, especially at high temperatures, but the presence of Zr and Si in titanium alloys can result in a mixed (TiZr) alloy. 6 S 3 It has been found that silicide particles form, leading to rapid loss of plastic elongation, loss of area, and loss of ballistic resistance. Therefore, in certain embodiments, the titanium alloy is substantially free of Zr to avoid these problems.
[0040] Tungsten (W) may increase the strength and creep strength of titanium alloys, but W has a relatively high density compared to Ti, so the addition of W may cause the alloy material to become inhomogeneous. Therefore, to avoid this problem, in certain embodiments, the titanium alloy is substantially free of W.
[0041] In certain embodiments, the titanium alloys described herein may be forged from a portion of a cylindrical billet in one or more steps into a shape approximating a finished turbine component below the beta transus, which is the temperature at which, upon heating, all of the low temperature alpha, close-packed hexagonal phase disappears and the high temperature beta, body-centered cubic phase exists. The forging temperature may be below the beta transus temperature of the titanium alloy and may vary from 14° C. to 83° C. below the beta transus temperature.
[0042] The forged shape may be solution heat treated at a temperature closer to the beta transus than the forging temperature to control the volume fraction of the primary alpha and beta phases. For example, the solution temperature can typically be varied from 17°C to 69°C below the beta transus temperature, and the solution time should be at least 1 hour.
[0043] It is well known that increasing the cooling rate after solution heat treatment can increase the 0.2% yield strength and ultimate tensile strength. For the purposes of this application, all alloys were solution heat treated and cooled at a rate of about 208°C / min, which corresponds to a cross-sectional size of about 80 mm for parts that were water-cooled from solution heat treatment. Thus, all tensile properties measured and reported here correspond to the tensile properties expected for parts with a cross-sectional size as large as 101.6 mm that are liquid quenched (water, oil, polymer, etc.) or gas cooled (air, helium, etc.) after solution heat treatment. It is well known that higher strength can be obtained by increasing the cooling rate after solution heat treatment. The cooling rate after melting at any location of the heat treated part may be measured directly using embedded thermocouples, estimated using finite element models, or a combination of both. The cooling rate after melting may be measured and / or calculated between about 28°C below the melting temperature and 83°C below the melting temperature.
[0044] After hot melt processing and cooling, the part may be overaged at 537.8°C to 760°C for at least 1.5 hours (e.g., 2 hours) to minimize residual stresses from hot melt processing and cooling while maintaining a balance of 0.2% yield strength, ultimate tensile strength, plastic elongation, reduction in area, and ballistic impact resistance. These processing methods may achieve desired properties for the titanium alloy, such as a 0.2% yield strength of 1000 MPa or greater (e.g., 1000 MPa to 1380 MPa), an ultimate tensile strength of 1060 MPa or greater (e.g., 1060 MPa to 1450 MPa), a plastic elongation of 15.0% or greater (e.g., 15.0% to 30.0%), a ballistic impact resistance as measured by a crack length of 3.048 mm or less (e.g., 0 mm to 3.048 mm), an area reduction of 45% RA or greater (e.g., 45% RA to 75% RA), or any combination of these properties as described above.
[0045] As previously mentioned, the titanium alloys described herein may be utilized in the formation of turbine components for use in an exemplary turbofan engine. FIG. 1 is a schematic diagram of an exemplary turbofan engine 10 having a central rotating shaft 12. In an exemplary embodiment, the turbofan engine 10 includes an air intake side 14 and an exhaust side 16. The turbofan engine 10 also includes a core gas turbine engine 18 including a high pressure compressor 20, a combustor 22, and a high pressure turbine 24. Additionally, the turbofan engine 10 includes a low pressure turbine 26 disposed axially downstream of the core gas turbine engine 18 and a fan assembly 28 disposed axially upstream of the core gas turbine engine 22. The fan assembly 28 includes an array of fan blades 30 extending radially outward from a rotor hub 32. Additionally, the turbofan engine 10 includes a first rotor shaft 34 disposed between the fan assembly 28 and the low pressure turbine 26, and a second rotor shaft 36 disposed between the high pressure compressor 20 and the high pressure turbine 24, with the fan assembly 28, the high pressure compressor 20, the high pressure turbine 24, and the low pressure turbine 26 being disposed in series and coaxially aligned with respect to the central rotational axis 12 of the turbofan engine 10.
[0046] During operation, air enters through the intake side 14 and flows through the fan assembly 28 into the high pressure compressor 20. The compressed air is delivered to the combustor 22. The airflow from the combustor 22 drives the high pressure turbine 24 and the low pressure turbine 26 before exiting the turbofan engine 10 through the exhaust side 16.
[0047] High pressure compressor 20, combustor 22, high pressure turbine 24, and low pressure turbine 26 each include at least one rotor assembly. The rotor assembly or rotor assemblies are generally exposed to different temperatures depending on their relative axial location within turbofan engine 10. For example, in the exemplary embodiment, turbofan engine 10 has generally lower operating temperatures toward the forward fan assembly 28 and higher operating temperatures toward the aft high pressure compressor 20. Thus, the rotor components within high pressure compressor 20 are generally manufactured from materials capable of withstanding higher temperatures as compared to the materials of manufacture of the rotor components of fan assembly 28.
[0048] The turbofan engine 10 represents one member of a class of rotary machines, other members of which include land-based gas turbines, turbojets, turboshaft engines, unducted engines, unducted fans, fixed wing and propeller rotors, and the like, as well as distributed propulsion devices, such as distributed fans or pods. Turbine components formed of the titanium alloys described herein can be in the form of rotary machine components useful for operating such rotary machines. Exemplary rotary machine components include, for example, disks, bladed disks, wings, blades, vanes, integrally bladed rotors, frames, fairings, seals, gearboxes, cases, mounts, shafts, and the like.
[0049] FIG. 2 illustrates an example of a turbine component that may be constructed from a titanium alloy, showing an isometric view of a single stage bladed disk 50, also known as an integrally bladed rotor. The bladed disk 50 has a hub 52 that surrounds a central axis of rotation 12, also referenced as the axis 12 of the turbofan engine 10 of FIG. 1. Extending generally radially from the hub 52 are blades 60. In the high pressure compressor 20 of FIG. 1, a bimetallic bladed disk may be preferred, where the hub 52 and the blades 60 are different alloys, to optimize the bladed disk for performance parameters such as fatigue life, FOD tolerance, creep strength, etc. The airfoil 60 is solid-phase welded to the hub 52 using a process such as translational or linear friction welding. It is therefore desirable to select a material that provides the hub 52 with good thick section properties and the airfoil 60 with good fatigue and FOD properties at a relatively small section size.
[0050] In the exemplary embodiment shown in FIG. 2, the hub 52 is made from a titanium alloy as described herein, and the airfoil 60 is made from a commercially available or conventional material having desirable fatigue life performance, such as Ti-64. After welding, the interface between the hub 52 and the airfoil 60 may be referred to as the weld or heat affected zone 70. In this zone 70, there is a mixture of hub and airfoil alloys and a variety of microstructures. This mixture of alloys and the variety of microstructures may compromise fatigue, FOD, etc., in thick sections of the blade disk 50.
[0051] In another exemplary embodiment, the hub 52 and airfoil 60 are both made from the same titanium alloy of the present disclosure, or from separate exemplary titanium alloys of the present disclosure. If the hub 52 and airfoil 60 are the same titanium alloy, then the hub and airfoil alloys are not intermingled in zone 70, but different microstructures are present. This different microstructures may again compromise fatigue, FOD, etc. in thick sections of portions of the blade disk 50.
[0052] To optimize mass of rotating components (by eliminating bolted joints) and utilize high temperature materials, adjacent stages of the blade disks may be inertia welded in the high pressure compressor 20 shown in FIG. 1. Similar to the bimetal hub / airfoil, it is desirable for the forward blade disk stage to be made of a first material and the aft blade disk stage to be made of a second material. As shown in FIG. 3, the forward blade disk stage 80 may be made of an exemplary titanium alloy of the present disclosure, and the aft blade disk stage 90 may be made of a conventional material, such as Ti-17. Again, there is a weld zone or heat affected zone 70, where there is a mix of the forward and aft blade disk alloys, and where there is a variety of microstructures in the zone 70, representing an area of reduced material properties.
[0053] In other exemplary embodiments, the adjacent forward blade disk stage 80 and aft blade disk stage 90 may both be made from the same titanium alloy of the present disclosure or from another exemplary titanium alloy of the present disclosure.
[0054] 2 and 3, any of the example titanium alloys of the present disclosure may be used alone or in combination with commercially available alloys for one or more of the airfoil 60, hub 52, blade disk 50, front stage blade disk 80, or rear stage blade disk 90. Although two stages are described in FIG. 3, more than two stages of blade disks are contemplated.
[0055] While materials may be selected based on these properties alone, consideration should be given to recovering material property losses due to the weld-induced thermal environment seen in translation friction welding or linear friction welding, for example, by post-treatment, such as furnace heat treatment. As described below, the disclosed titanium alloys are compatible with commercially available titanium alloys, allowing manufacturers to maximize the benefits of this bimetallic material property by better matching heat treatment temperatures and treatments, for example, between the hub 52 material and the airfoil 60 material, and between the materials of the adjacent blade disk stages 80, 90. These benefits can be realized not only with commercially available titanium alloys, but also when the titanium alloy of the present invention is welded to itself. For translation friction welded bimetallic blade disks, using the disclosed titanium alloy as the hub and Ti-64 as the airfoil instead of beta-treated Ti-17 or beta-treated Ti-6246 improves flow stress and microstructural compatibility between the titanium alloy of the hub and the Ti-64 alloy airfoil. This may result in a solid weld that is less prone to defect formation during or after the welding process.
[0056] Exemplary parts may have thick sections, be cast and forged, structural aerospace castings, and the like.
[0057] [Example] Exemplary alloys (E-1 through E-20) were made according to the chemical compositions shown in Table 1. These exemplary alloys were formed by an open-die forging process designed to replicate the typical production billet conversion process. First, the as-cast ingots were hot worked above the beta transus, then subtransus hot worked, and the material was then reheated above the beta transus for further hot working, followed by a water quench to induce beta recrystallization. Finally, the material was reheated below the beta transus and hot worked to the final diameter. All hot working was performed using the same open-die forging used in the large-scale production ingot-to-billet processing so that the microstructure and texture of the subscale material would be representative of the larger production scale material.
[0058] The comparative alloys are described below and shown in Tables 2, 3A, and 3B. The alloys in Tables 1, 2, 3A, and 3B were cooled from an α+β hot melt process at 208°C / min. These alloys were measured to determine 0.2% YS, UTS, % plastic elongation, and % reduction in area according to ASTM E8 / E8M at 23°C.
[0059] The 0.2% YS data at 23°C for the alloys shown in Table 1 were entered into a multiple linear regression statistical model using a commercially available statistical analysis package (MiniTab V.20.2). The elements: Al, O, Fe, Si, and Mo were determined to be statistically significant using p-tests with a confidence level of greater than 95% for the statistical significance of each element. The prediction model for yield strength is shown in Equation 1. [Formula 1]0.2%YS(MPa)=469.3+48.8*Al(weight%)+748*O(weight%)+96.1*Fe(weight%)+188*Si(weight%)+57.7*Mo(weight%)
[0060] For high strength Ti alloy applications, candidate alloys should have a 0.2% YS of 1000 MPa or greater at 23°C.
[0061] The 23°C UTS data for the alloys shown in Table 1 were entered into a multiple linear regression statistical model using a commercially available statistical analysis package (MiniTab V.20.2). The elements: Al, O, Fe, Si, and Mo were determined to be statistically significant using p-tests with a confidence level of greater than 95% for the statistical significance of each element. The prediction model for ultimate tensile strength is shown in Equation 2. [Formula 2] UTS(Mpa)=612.1+39.2*Al(weight%)+666*O(weight%)+74.6*Fe(weight%)+202*Si(weight%)+41.6Mo(weight%)
[0062] For high strength Ti alloy applications, candidate alloys should have a UTS of 1060 MPa or greater at 23°C.
[0063] The percent plastic elongation (%EL) at 23°C for the alloys shown in Table 1 was entered into a multiple linear regression statistical model using a commercially available statistical analysis package (MiniTab V20.2). Note that statistical analysis was performed using a Log(10) transformation of the %plastic elongation values, similar to the standard method for log-normally distributed data (J Chen, Z Wang et al., Int. J. Plast.152(2022)103260). The elements: Fe, Si, and Mo were determined to be statistically significant using p-tests with a confidence level of greater than 95% for the statistical significance of each element. The prediction model for yield strength is shown in Equation 3. [Formula 3]EL(%)=10^(1.149+0.211*Fe(weight%)-0.514*Si(weight%)+0.076*Mo(weight%))
[0064] For high strength Ti alloy applications, it is desirable for candidate alloys to have a plastic elongation of 15.0% or greater at 23°C.
[0065] The percent area reduction (%RA) at 23°C for the alloys shown in Table 1 was entered into a multiple linear regression statistical model using a commercially available statistical analysis package (MiniTab V20.2). The statistical analysis was performed using a Log(10) transformation of the % reduction in area values, similar to the standard method for log-normally distributed data (J Chen, Z Wang et al., Int. J. Plast.152(2022)103260). The elements: Fe, Si, and Mo were determined to be statistically significant using p-tests with a confidence level of greater than 95% for the statistical significance of each element. The prediction model for yield strength is shown in Equation 4. [Formula 4]RA(%)=10^(1.560+0.195*Fe(weight%)-0.663*Si(weight%)+0.139*Mo(weight%))
[0066] For high-strength Ti alloy applications, it is desirable for candidate alloys to have an area reduction rate of 45.0% or more at 23°C.
[0067] In certain embodiments, it is desirable for high strength Ti alloys to have both high strength (1000 MPa 0.2% YS or greater, according to Equation 1) and high % plastic elongation (15.0% or greater, according to Equation 3).
[0068] Comparative alloys (C-1 through C-20) were also prepared according to the chemical compositions shown in Table 2. These comparative alloys were open die forged in the same manner as the exemplary alloys in Table 1. The alloys in Table 2 were each measured for their properties at 23°C according to ASTM E8 / E8M. As shown by the results in Table 2, these comparative alloys did not meet the desired titanium alloy specifications.
[0069] Comparative alloys C-21 through C-50 were also made according to the chemical compositions shown in Table 3A, and comparative alloys C-51 through C-66 were also made according to the chemical compositions shown in Table 3B. As shown by the results in Tables 3A and 3B, these comparative alloys did not meet the desired titanium alloy specifications.
[0070] The alloy data from US Patent Publication No. 2017 / 0268091 is shown in Table 4 as comparative alloys (Comp-A through Comp-M). The alloys in Table 4 were cast as ingots and then extruded to final size in the alpha / beta phase field without following the typical open die forging billet process. This extrusion process may result in a different combination of 0.2% yield strength, ultimate tensile strength, % plastic elongation, and % area reduction due to the texture differences induced by the extrusion process. This process is quite different from what may be used in large scale manufacturing production. Thus, alloy Comp-G meets some of the target alloy properties, but has a lower predicted elongation as an alloy processed according to the open die forge process used for the exemplary alloys in Table 1. Thus, alloy Comp-G is believed to be an alloy with less elongation during large scale processing than shown in Table 4. Alloy Comp-J meets some of the target alloy properties, but the copper content makes large scale use of alloy Comp-J problematic. That is, the presence of copper causes severe segregation during solidification of large diameter ingots, leading to large scale production chemistry and microstructure control problems.
[0071] [Table 1]
[0072] [Table 2]
[0073] [Table 3A]
[0074] [Table 3B]
[0075] [Table 4]
[0076] Further aspects are provided by the subject matter of the following clauses.
[0077] 1. A turbine component comprising a titanium alloy, the titanium alloy comprising: 5.50% to 6.90% by weight aluminum, 3.50% to 4.50% by weight vanadium, 0.01% to 0.03% by weight carbon, 0.20% to 0.70% by weight iron, 1.00% to 1.50% by weight molybdenum, 0.10% to 0.30% by weight silicon, up to 0.21% by weight oxygen, up to 0.016% by weight nitrogen (e.g., up to 0.015% by weight nitrogen), and balance titanium, the titanium alloy being substantially free of copper.
[0078] 1. A turbine component comprising a titanium alloy, the titanium alloy comprising 5.50% to 6.90% by weight aluminum, 3.50% to 4.50% by weight vanadium, 0.01% to 0.03% by weight carbon, 0.20% to 0.70% by weight iron, 1.00% to 1.50% by weight molybdenum, 0.10% to 0.30% by weight silicon, up to 0.21% by weight oxygen, up to 0.016% by weight nitrogen (e.g., up to 0.015% by weight nitrogen), and the balance titanium ... Fe, Si, Mo are present in amounts to provide a predicted 0.2% yield strength at 23°C of 1000 MPa or greater according to the formula: 469.3 + 48.8 * Al (wt%) + 748 * O (wt%) + 96.1 * Fe (wt%) + 188 * Si (wt%) + 57.7 * Mo (wt%) and / or Fe, Si, Mo are present in amounts to provide a predicted % plastic elongation at 23°C of 15.0% or greater according to the formula: 10^ (1.149 + 0.211 * Fe (wt%) - 0.514 * Si (wt%) + 0.076 * Mo (wt%)).
[0079] The turbine component of any preceding clause, wherein the titanium alloy is substantially free of copper.
[0080] 13. The turbine component of any preceding clause, wherein the titanium alloy has a 0.2% yield strength of 1000 MPa or greater.
[0081] 23. The turbine component according to any preceding clause, wherein the titanium alloy has a 0.2% yield strength of 1000 MPa to 1380 MPa.
[0082] 4. The turbine component of any preceding clause, wherein the titanium alloy has an ultimate tensile strength of 1060 MPa or greater.
[0083] 23. The turbine component of any preceding clause, wherein the titanium alloy has an ultimate tensile strength of 1060 MPa to 1450 MPa.
[0084] The turbine component of any preceding clause, wherein the titanium alloy has a plastic elongation of 15.0% or greater.
[0085] 13. The turbine component of any preceding clause, wherein the titanium alloy has a plastic elongation of 15.0% to 30.0%.
[0086] The turbine component of any preceding clause, wherein the titanium alloy has a ballistic impact resistance as measured by a crack length of 3.048 mm or less.
[0087] The turbine component of any preceding clause, wherein the titanium alloy has a ballistic impact resistance as measured by a crack length of between 0 mm and 3.048 mm.
[0088] The turbine component of claim 1 , wherein the turbine component has an area reduction of 45% RA or greater.
[0089] 2. The turbine component according to any one of the preceding clauses, wherein the area reduction rate of the turbine component is 45% RA to 75% RA.
[0090] 13. The turbine component of any preceding clause, wherein the titanium alloy has a 0.2% yield strength of 1000 MPa or more, an ultimate tensile strength of 1060 MPa or more, a plastic elongation of 15.0% or more, and a reduction in area of 45%RA or more.
[0091] 13. The turbine component according to any one of the preceding clauses, wherein the titanium alloy has a 0.2% yield strength of 1000 MPa to 1380 MPa, an ultimate tensile strength of 1060 MPa to 1450 MPa, a ductility of 15.0% to 30.0%, and an area reduction rate of 45% RA to 75% RA.
[0092] The turbine component of any preceding clause, wherein the titanium alloy is substantially free of chromium.
[0093] The turbine component of any preceding clause, wherein the titanium alloy is substantially tin-free.
[0094] The turbine component of any preceding clause, wherein the titanium alloy is substantially free of nickel.
[0095] The turbine component of any preceding clause, wherein the titanium alloy is substantially free of zirconium.
[0096] The turbine component of any preceding clause, wherein the titanium alloy is substantially free of tungsten.
[0097] 13. The turbine component of any preceding claim, wherein the titanium alloy is substantially free of other elements.
[0098] 11. The turbine component of any preceding clause, wherein Al, O, Fe, Si and Mo are present in amounts such that a 0.2% yield strength at 23°C predicted according to the formula: 469.3 + 48.8 * Al(wt%) + 748 * O(wt%) + 96.1 * Fe(wt%) + 188 * Si(wt%) + 57.7 * Mo(wt%) is equal to or greater than 1000 MPa.
[0099] The turbine component of any preceding clause, wherein Fe, Si, and Mo are present in amounts such that the % plastic elongation at 23°C predicted according to the formula: 10^(1.149+0.211*Fe(wt%)-0.514*Si(wt%)+0.076*Mo(wt%) is 15.0% or greater.
[0100] The turbine component of any preceding clause, wherein Al, O, Fe, Si, and Mo are present in amounts to provide a 0.2% yield strength at 23°C of 1000 MPa or greater as predicted according to the formula: 469.3 + 48.8 * Al (wt%) + 748 * O (wt%) + 96.1 * Fe (wt%) + 188 * Si (wt%) + 57.7 * Mo (wt%), and wherein Fe, Si, and Mo are present in amounts to provide a % plastic elongation at 23°C of 15.0% or greater as predicted according to the formula: 10^ (1.149 + 0.211 * Fe (wt%) - 0.514 * Si (wt%) + 0.076 * Mo (wt%)).
[0101] 13. The turbine component of any preceding clause, wherein the titanium alloy comprises 3.80% to 4.43% vanadium by weight.
[0102] 7. The turbine component of any preceding clause, wherein the titanium alloy comprises 0.45% to 0.57% by weight iron.
[0103] 13. The turbine component of any preceding clause, wherein the titanium alloy comprises 0.14% to 0.28% by weight silicon.
[0104] The turbine component of any preceding clause, wherein the titanium alloy consists essentially of 5.50% to 6.90% by weight aluminum, 3.50% to 4.50% by weight vanadium, 0.01% to 0.03% by weight carbon, 0.20% to 0.70% by weight iron, 1.00% to 1.50% by weight molybdenum, 0.10% to 0.30% by weight silicon, up to 0.21% by weight oxygen, up to 0.016% by weight nitrogen (e.g., up to 0.015% by weight nitrogen), and the balance titanium.
[0105] The turbine component of any preceding clause, wherein the titanium alloy consists essentially of 5.50-6.90 wt.% aluminum, 3.50-4.50 wt.% vanadium, 0.01-0.03 wt.% carbon, 0.20-0.70 wt.% iron, 1.00-1.50 wt.% molybdenum, 0.10-0.30 wt.% silicon, up to 0.21 wt.% oxygen, up to 0.016 wt.% nitrogen (e.g., up to 0.015 wt.% nitrogen), and the balance titanium.
[0106] 1. A turbine component made of a titanium alloy, the titanium alloy consisting essentially of, by weight, 5.50% to 6.90% aluminum, 3.50% to 4.50% vanadium, 0.01% to 0.03% carbon, 0.20% to 0.70% iron, 1.00% to 1.50% molybdenum, 0.10% to 0.30% silicon, up to 0.21% oxygen, up to 0.016% nitrogen (e.g., up to 0.015% nitrogen), and the balance titanium.
[0107] A turbine component made of a titanium alloy, the titanium alloy consisting of 5.50-6.90 weight percent aluminum, 3.50-4.50 weight percent vanadium, 0.01-0.03 weight percent carbon, 0.20-0.70 weight percent iron, 1.00-1.50 weight percent molybdenum, 0.10-0.30 weight percent silicon, up to 0.21 weight percent oxygen, up to 0.016 weight percent nitrogen (e.g., up to 0.015 weight percent nitrogen), and the balance titanium.
[0108] 13. The turbine component of any preceding clause, wherein the titanium alloy has a 0.2% yield strength of 1000 MPa or greater.
[0109] 23. The turbine component according to any preceding clause, wherein the titanium alloy has a 0.2% yield strength of 1000 MPa to 1380 MPa.
[0110] 4. The turbine component of any preceding clause, wherein the titanium alloy has an ultimate tensile strength of 1060 MPa or greater.
[0111] 23. The turbine component of any preceding clause, wherein the titanium alloy has an ultimate tensile strength of 1060 MPa to 1450 MPa.
[0112] The turbine component of any preceding clause, wherein the titanium alloy has a plastic elongation of 15.0% or greater.
[0113] 13. The turbine component of any preceding clause, wherein the titanium alloy has a plastic elongation of 15.0% to 30.0%.
[0114] The turbine component of any preceding clause, wherein the titanium alloy has a ballistic impact resistance as measured by a crack length of 3.048 mm or less.
[0115] 2. The turbine component of any preceding clause, wherein the titanium alloy has a ballistic impact resistance as measured by a crack length of between 0 mm and 3.048 mm.
[0116] The turbine component of any preceding clause, wherein the turbine component has an area reduction of 45% RA or greater.
[0117] 2. The turbine component according to any preceding clause, wherein the turbine component has an area reduction rate of 45% RA to 75% RA.
[0118] 13. The turbine component of any preceding clause, wherein the titanium alloy has a 0.2% yield strength of 1000 MPa or more, an ultimate tensile strength of 1060 MPa or more, a plastic elongation of 15.0% or more, a crack length of 3.048 mm or less, and a reduction in area of 45% RA or more.
[0119] 11. The turbine component according to any of the preceding clauses, wherein the titanium alloy has a 0.2% yield strength of 1000 MPa to 1380 MPa, an ultimate tensile strength of 1060 MPa to 1450 MPa, a ductility of 15.0% to 30.0%, a ballistic impact resistance measured at a crack length of 0 to 3.048 mm, and an area reduction of 45% RA to 75% RA.
[0120] A method of forming a turbine component as defined in any preceding clause.
[0121] 1. A method of forming a turbine component, comprising forging a titanium alloy into a turbine component, the titanium alloy consisting of: 5.50% to 6.90% aluminum, 3.50% to 4.50% vanadium, 0.01% to 0.03% carbon, 0.20% to 0.70% iron, 1.00% to 1.50% molybdenum, 0.10% to 0.30% silicon, up to 0.21% oxygen, up to 0.016% nitrogen (e.g., up to 0.015% nitrogen), and balance titanium, wherein the titanium alloy is substantially free of copper.
[0122] 1. A method of forming a turbine component, comprising forging a titanium alloy into the turbine component, the titanium alloy comprising, by weight, 5.50% to 6.90% aluminum, 3.50% to 4.50% vanadium, 0.01% to 0.03% carbon, 0.20% to 0.70% iron, 1.00% to 1.50% molybdenum, 0.10% to 0.30% silicon, up to 0.21% oxygen, up to 0.016% nitrogen (e.g., up to 0.015% nitrogen), and the balance titanium, with Al, O, F 1. A method of forming a turbine component, wherein e, Si, and Mo are present in amounts to provide a 0.2% yield strength at 23°C of 1000 MPa or greater as predicted according to the formula: 469.3+48.8*Al(wt%)+748*O(wt%)+96.1*Fe(wt%)+188*Si(wt%)+57.7*Mo(wt%), and / or Fe, Si, and Mo are present in amounts to provide a plastic elongation at 23°C of 15.0% or greater as predicted according to the formula: 10^(1.149+0.211*Fe(wt%)-0.514*Si(wt%)+0.076*Mo(wt%).
[0123] The method of any preceding clause, wherein forging the titanium alloy into the turbine component includes forging the titanium alloy at a forging temperature below a beta transus temperature of the titanium alloy.
[0124] 13. The method of any preceding clause, comprising heat treating the titanium alloy.
[0125] 13. The method of any preceding clause comprising hot melt treating the titanium alloy at a heat treatment temperature below the beta transus temperature of the titanium alloy.
[0126] The method of any preceding clause, wherein the heat treatment temperature exceeds the forging temperature and the titanium alloy is held at the heat treatment temperature for at least one hour.
[0127] The method of any preceding clause, comprising heat treating the titanium alloy and then cooling the titanium alloy to form the turbine component.
[0128] The method of any preceding clause, wherein cooling of the titanium alloy is performed at a cooling rate of 208°C / min from the heat treatment temperature.
[0129] 2. The method of any preceding clause, further comprising the step of heating the titanium alloy to a superheat treatment temperature of 538°C to 760°C for at least 1.5 hours after hot melt treatment and cooling.
[0130] 2. The method according to any preceding clause, wherein the titanium alloy has a 0.2% yield strength of 1000 MPa or more.
[0131] 2. The method according to any preceding clause, wherein the ultimate tensile strength of the titanium alloy is 1060 MPa or greater.
[0132] 2. The method of any preceding clause, wherein the plastic elongation of the titanium alloy is 15.0% or greater.
[0133] The method of any preceding clause, wherein the titanium alloy has a ballistic impact resistance, as measured by crack length, of 3.048 mm or less.
[0134] 2. The method according to any preceding clause, wherein the area reduction rate of the titanium alloy is 45% or more.
[0135] 2. A titanium alloy formed according to the method of any preceding clause.
[0136] This written description uses examples to disclose the disclosure, including the best mode, and also to enable any person skilled in the art to practice the disclosure, including making and using any device or system, and performing any incorporated methods. The patentable scope of the disclosure is defined by the claims, and may include other examples that occur to those skilled in the art. Such other examples are deemed to be within the scope of the claims if they contain structural elements that do not differ from the claim language, or if they contain equivalent structural elements that do not differ insubstantial from the claim language. [Explanation of symbols]
[0137] 10. Turbofan engine 12 Rotation axis 14 Intake side 16 Exhaust side 18 Core Gas Turbine Engine 20 High Pressure Compressor 22 Combustor, core gas turbine engine 23 Predictions 24 High Pressure Turbine 26 Low Pressure Turbine 28 Fan Assembly 30 Fan Blades 32 rotor hub 34 First rotor shaft 36 Second rotor shaft 50 Blade Disc 52 Hub 60 airfoil 70 Heat Affected Zone 80 Front blade disc 90 Rear blade disc
Claims
1. 1. A turbine component made of a titanium alloy, comprising: The titanium alloy is 5.50% to 6.90% by weight of aluminum; 3.50% to 4.50% by weight vanadium; 0.01% to 0.03% by weight carbon; 0.20% to 0.70% by weight of iron; 1.00% to 1.50% by weight of molybdenum; 0.10% to 0.30% by weight of silicon; up to 0.21 wt. % oxygen; up to 0.016 wt. % nitrogen; The remaining titanium, It is composed of The turbine component, wherein the titanium alloy is substantially free of copper.
2. 1. A turbine component made of a titanium alloy, comprising: The titanium alloy is 5.50% to 6.90% by weight of aluminum; 3.50% to 4.50% by weight vanadium; 0.01% to 0.03% by weight carbon; 0.20% to 0.70% by weight of iron; 1.00% to 1.50% by weight of molybdenum; 0.10% to 0.30% by weight of silicon; up to 0.21 wt. % oxygen; up to 0.016 wt. % nitrogen; The remaining titanium, It is composed of Al, O, Fe, Si, Mo are present in amounts such that the 0.2% yield strength at 23° C. predicted according to the formula: 469.3 + 48.8 * Al (wt%) + 748 * O (wt%) + 96.1 * Fe (wt%) + 188 * Si (wt%) + 57.7 * Mo (wt%) is less than or equal to 1000 MPa; or A turbine component, wherein Fe, Si, and Mo are present in amounts such that the predicted plastic elongation at 23°C is 15.0% or greater according to the formula: 10^(1.149 + 0.211 * Fe(wt%) - 0.514 * Si(wt%) + 0.076 * Mo(wt%)).
3. The turbine component of claim 1 or 2, wherein the titanium alloy is substantially free of copper.
4. The turbine component according to any one of claims 1 to 3, wherein the titanium alloy has a 0.2% yield strength of 1000 MPa or more.
5. A turbine component according to any one of the preceding claims, wherein the titanium alloy has a 0.2% yield strength of between 1000 MPa and 1380 MPa.
6. A turbine component according to any preceding claim, wherein the titanium alloy has an ultimate tensile strength of at least 1060 MPa.
7. A turbine component according to any preceding claim, wherein the titanium alloy has an ultimate tensile strength of between 1060 MPa and 1450 MPa.
8. The turbine component according to any one of the preceding claims, wherein the titanium alloy has a plastic elongation of at least 15.0%.
9. A turbine component according to any preceding claim, wherein the titanium alloy has a plastic elongation of between 15.0% and 30.0%.
10. The turbine component of any one of claims 1 to 9, wherein the titanium alloy has a ballistic impact resistance as measured by a crack length of 3.048 mm or less.
11. A turbine component according to any preceding claim, wherein the titanium alloy has a ballistic impact resistance as measured by a crack length of between 0 mm and 3.048 mm.
12. The turbine component according to any one of the preceding claims, wherein the area reduction of the turbine component is at least 45% RA.
13. A turbine component according to any one of the preceding claims, wherein the area reduction of the turbine component is between 45% RA and 75% RA.
14. The turbine component of any one of claims 1 to 13, wherein the titanium alloy has a 0.2% yield strength of 1000 MPa or more, an ultimate tensile strength of 1060 MPa or more, a plastic elongation of 15.0% or more, and a reduction in area of 45% RA or more.
15. 15. The turbine component of any one of claims 1 to 14, wherein the titanium alloy has a 0.2% yield strength of 1000 MPa to 1380 MPa, an ultimate tensile strength of 1060 MPa to 1450 MPa, a ductility of 15.0% to 30.0%, and a reduction in area of 45% RA to 75% RA.
16. A turbine component according to any preceding claim, wherein the titanium alloy is substantially free of chromium.
17. A turbine component according to any preceding claim, wherein the titanium alloy is substantially free of tin.
18. A turbine component according to any preceding claim, wherein the titanium alloy is substantially free of nickel.
19. A turbine component according to any preceding claim, wherein the titanium alloy is substantially free of zirconium.
20. A turbine component according to any preceding claim, wherein the titanium alloy is substantially free of tungsten.
21. A turbine component according to any preceding claim, wherein the titanium alloy is substantially free of other elements.
22. 22. A turbine component according to any one of the preceding claims, wherein Al, O, Fe, Si and Mo are present in amounts to provide a 0.2% yield strength at 23°C predicted according to the formula: 469.3 + 48.8*Al(wt%) + 748*O(wt%) + 96.1*Fe(wt%) + 188*Si(wt%) + 57.7*Mo(wt%) of at least 1000 MPa.
23. 23. A turbine component according to any one of claims 1 to 22, wherein Fe, Si and Mo are present in amounts such that the plastic elongation at 23°C predicted according to the formula: 10^(1.149 + 0.211 * Fe(wt%) - 0.514 * Si(wt%) + 0.076 * Mo(wt%)) is 15.0% or greater.
24. 24. A turbine component according to any one of claims 1 to 23, wherein Al, O, Fe, Si, Mo are present in amounts to provide a 0.2% yield strength at 23°C predicted according to the formula: 469.3 + 48.8 * Al(wt%) + 748 * O(wt%) + 96.1 * Fe(wt%) + 188 * Si(wt%) + 57.7 * Mo(wt%) of 1000 MPa or greater, and further wherein Fe, Si, Mo are present in amounts to provide a plastic elongation at 23°C predicted according to the formula: 10^ (1.149 + 0.211 * Fe(wt%) - 0.514 * Si(wt%) + 0.076 * Mo(wt%)) of 15.0% or greater.
25. A turbine component according to any preceding claim, wherein the titanium alloy comprises between 3.80% and 4.43% vanadium by weight.
26. A turbine component according to any preceding claim, wherein the titanium alloy comprises between 0.45% and 0.57% by weight iron.
27. A turbine component according to any preceding claim, wherein the titanium alloy comprises between 0.14% and 0.28% by weight silicon.
28. The titanium alloy is 5.50% to 6.90% by weight of aluminum; 3.50% to 4.50% by weight vanadium; 0.01% to 0.03% by weight carbon; 0.20% to 0.70% by weight of iron; 1.00% to 1.50% by weight of molybdenum; 0.10% to 0.30% by weight of silicon; up to 0.21 wt. % oxygen; up to 0.016 wt. % nitrogen; The remaining titanium, The turbine component of any one of claims 1 to 27, consisting essentially of
29. The titanium alloy is 5.50% to 6.90% by weight of aluminum; 3.50% to 4.50% by weight vanadium; 0.01% to 0.03% by weight carbon; 0.20% to 0.70% by weight of iron; 1.00% to 1.50% by weight of molybdenum; 0.10% to 0.30% by weight of silicon; up to 0.21 wt. % oxygen; up to 0.016 wt. % nitrogen; A turbine component according to any preceding claim, comprising a composition with the remainder being titanium.
30. 1. A turbine component made of a titanium alloy, comprising: The titanium alloy is 5.50% to 6.90% by weight of aluminum; 3.50% to 4.50% by weight vanadium; 0.01% to 0.03% by weight carbon; 0.20% to 0.70% by weight of iron; 1.00% to 1.50% by weight of molybdenum; 0.10% to 0.30% by weight of silicon; up to 0.21 wt. % oxygen; up to 0.016 wt. % nitrogen; The remaining titanium, Turbine components are basically composed of:
31. 1. A turbine component made of a titanium alloy, comprising: The titanium alloy is 5.50% to 6.90% by weight of aluminum; 3.50% to 4.50% by weight vanadium; 0.01% to 0.03% by weight carbon; 0.20% to 0.70% by weight of iron; 1.00% to 1.50% by weight of molybdenum; 0.10% to 0.30% by weight of silicon; up to 0.21 wt. % oxygen; up to 0.016 wt. % nitrogen; The remaining titanium, 1. A turbine component, comprising:
32. A turbine component according to any preceding claim, wherein the titanium alloy has a 0.2% yield strength of at least 1000 MPa.
33. A turbine component according to any preceding claim, wherein the titanium alloy has a 0.2% yield strength of between 1000 MPa and 1380 MPa.
34. A turbine component according to any preceding claim, wherein the titanium alloy has an ultimate tensile strength of at least 1060 MPa.
35. A turbine component according to any preceding claim, wherein the titanium alloy has an ultimate tensile strength of between 1060 MPa and 1450 MPa.
36. A turbine component according to any preceding claim, wherein the titanium alloy has a plastic elongation of at least 15.0%.
37. A turbine component according to any preceding claim, wherein the titanium alloy has a plastic elongation of between 15.0% and 30.0%.
38. A turbine component according to any preceding claim, wherein the titanium alloy has a ballistic impact resistance as measured by a crack length of 3.048 mm or less.
39. A turbine component according to any preceding claim, wherein the titanium alloy has a ballistic impact resistance as measured by a crack length of between 0mm and 3.048mm.
40. The turbine component of any one of the preceding claims, wherein the turbine component has an area reduction of at least 45% RA.
41. A turbine component according to any preceding claim, wherein the area reduction of the turbine component is between 45% RA and 75% RA.
42. 42. The turbine component of any one of claims 1 to 41, wherein the titanium alloy has a 0.2% yield strength of 1000 MPa or more, an ultimate tensile strength of 1060 MPa or more, a plastic elongation of 15.0% or more, a crack length of 3.048 mm or less, and a reduction in area of 45% RA or more.
43. 43. The turbine component of any one of claims 1 to 42, wherein the titanium alloy has a 0.2% yield strength of 1000 MPa to 1380 MPa, an ultimate tensile strength of 1060 MPa to 1450 MPa, a ductility of 15.0% to 30.0%, a ballistic impact resistance as measured by a crack length of 0 to 3.048 mm, and a reduction in area of 45% RA to 75% RA.
44. A method of forming a turbine component according to any preceding claim.
45. 1. A method of forming a turbine component, the method including forging a titanium alloy into the turbine component; The titanium alloy is 5.50% to 6.90% by weight of aluminum; 3.50% to 4.50% by weight vanadium; 0.01% to 0.03% by weight carbon; 0.20% to 0.70% by weight of iron; 1.00% to 1.50% by weight of molybdenum; 0.10% to 0.30% by weight of silicon; up to 0.21 wt. % oxygen; up to 0.016 wt. % nitrogen; The remaining titanium, It is composed of The method, wherein the titanium alloy is substantially free of copper.
46. 1. A method of forming a turbine component, the method including forging a titanium alloy into the turbine component; The titanium alloy is 5.50% to 6.90% by weight of aluminum; 3.50% to 4.50% by weight vanadium; 0.01% to 0.03% by weight carbon; 0.20% to 0.70% by weight of iron; 1.00% to 1.50% by weight of molybdenum; 0.10% to 0.30% by weight of silicon; up to 0.21 wt. % oxygen; up to 0.016 wt. % nitrogen; The remaining titanium, It is composed of Al, O, Fe, Si, Mo are present in amounts such that the 0.2% yield strength at 23° C. predicted according to the formula: 469.3 + 48.8 * Al (wt%) + 748 * O (wt%) + 96.1 * Fe (wt%) + 188 * Si (wt%) + 57.7 * Mo (wt%) is 1000 MPa or greater; or The method wherein Fe, Si, and Mo are present in amounts such that the predicted plastic elongation at 23°C according to the formula: 10^(1.149 + 0.211 * Fe (wt%) - 0.514 * Si (wt%) + 0.076 * Mo (wt%)) is 15.0% or greater.
47. 47. The method of claim 45 or 46, wherein forging the titanium alloy into the turbine component comprises forging the titanium alloy at a forging temperature below a beta transus temperature of the titanium alloy.
48. 48. The method of any one of claims 45 to 47, wherein the method includes heat treating the titanium alloy.
49. 48. The method of any one of claims 45 to 47, comprising hot melt processing the titanium alloy at a heat treatment temperature below the beta transus temperature of the titanium alloy.
50. 50. The method of claim 49, wherein the heat treatment temperature is at or above the forging temperature, and the titanium alloy is held at the heat treatment temperature for at least one hour.
51. 48. The method of any one of claims 45 to 47, the method including heat treating the titanium alloy and then cooling the titanium alloy to form the turbine component.
52. 48. The method of any one of claims 45 to 47, wherein the step of cooling the titanium alloy is performed at a cooling rate of 208°C / min from the heat treatment temperature.
53. 48. The method of any one of claims 45 to 47, further comprising the step of heating the titanium alloy to a superheat treatment temperature of 538°C to 760°C for at least 1.5 hours after hot melt treatment and cooling.
54. 48. The method of any one of claims 45 to 47, wherein the titanium alloy has a 0.2% yield strength of 1000 MPa or greater.
55. 48. The method of any one of claims 45 to 47, wherein the titanium alloy has an ultimate tensile strength of 1060 MPa or greater.
56. 48. The method of any one of claims 45 to 47, wherein the titanium alloy has a plastic elongation of 15.0% or greater.
57. 48. The method of any one of claims 45 to 47, wherein the titanium alloy has a ballistic impact resistance as measured by a crack length of 3.048 mm or less.
58. 48. The method of any one of claims 45 to 47, wherein the titanium alloy has an area reduction of 45% RA or greater.
